Oxygen-doped carbon material catalyst as well as preparation method and application thereof

The preparation of oxygen-doped carbon material catalysts through ozone oxidation solves the problems of high energy consumption and high cost of precious metal catalysts in the hydrogen peroxide production process, and achieves efficient and safe hydrogen peroxide production. The catalyst selectivity reaches 91%, which is suitable for large-scale applications.

CN119307969APending Publication Date: 2025-01-14NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411487986.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, hydrogen peroxide (H2O2) production process has high energy consumption, complicated steps and side reaction risks, and precious metal catalysts are costly and difficult to apply on a large scale. The 2e-ORR selectivity of carbon material oxidation method is insufficient, accompanied by secondary pollution. .

Method used

The carbon material is oxidized by ozone oxidation method, the ozone concentration, temperature and humidity are adjusted, and the oxygen-doped carbon material catalyst is prepared for electrocatalytic oxygen reduction reactions to achieve efficient production of hydrogen peroxide.

Benefits of technology

Prepare highly efficient 2e-ORR electrocatalyst under mild conditions, which is low cost, safe and reliable, has excellent catalyst performance and a selectivity of 91%. It is suitable for large-scale production and application without secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307969A_ABST
    Figure CN119307969A_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen-doped carbon material catalyst as well as a preparation method and application thereof. The method comprises the following steps: firstly, grinding a carbon material, and then putting the ground carbon material into a reaction container; and continuously introducing ozone into the reaction container, adjusting the temperature and the relative humidity of the reaction, and oxidizing the carbon material to obtain the oxygen-doped carbon material catalyst after the oxidation is completed. The oxygen-doped carbon material catalyst can be applied to preparation of hydrogen peroxide through an electrocatalytic oxygen reduction reaction. An ozone oxidation method is adopted, the proportion of oxygen-containing functional groups in the carbon material is accurately regulated and controlled by adjusting ozone concentration, reaction time, gas humidity and other conditions, the oxidation degree is controlled, and the catalytic performance of the carbon material is adjusted and optimized. Ozone oxidation reaction conditions are mild, and changes of functional groups on the surface of the catalyst can be monitored in real time in the reaction process. And meanwhile, the characteristics of high specific surface area and high conductivity of the carbon material are kept, and the efficient electrocatalytic activity can be developed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalysts, and in particular to an oxygen-doped carbon material catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen peroxide (H2O2) is an important chemical substance that is widely used in industry, medicine, military industry, food, environmental protection and other fields. Since H2O2 has dual functionality of oxidation and reduction and does not produce secondary pollution during use, it is defined as a green chemical product. At present, large-scale industrial production of H2O2 still relies on the traditional anthraquinone method, and about 99% of H2O2 is produced based on this process each year. However, the process of preparing H2O2 by the anthraquinone method is not only energy-intensive and cumbersome, but also produces a large amount of organic waste. A method of producing H2O2 that is considered to be green and simple is the direct synthesis of H2 and O2 under the action of a catalyst, but this process has both side reactions and the risk of explosion. In recent years, the electrochemical two-electron oxygen reduction reaction (2e - The synthesis of H2O2 by the ORR process has been widely studied as a promising reaction pathway. However, since the oxygen reduction reaction has another four-electron process in which water is the product, namely 2e - The competitive reaction of ORR, therefore, is to design 2e with high selectivity. - ORR catalysts are of great significance.

[0003] So far, the main research on 2e - ORR electrocatalysts are noble metals and their alloys, including Au, Pt, Pd-Au, Pt-Hg, and Pd-Hg. However, the high cost of noble metal materials and the harsh preparation conditions have greatly hindered their large-scale application.

[0004] As a material with low density, high porosity, large specific surface area and strong conductivity, carbon materials are widely used in adsorption, energy conversion and storage, capacitors and catalysts. In recent years, heteroatom-doped carbon materials obtained by various modification strategies have been widely reported, among which oxygen-doped carbon materials obtained by controlled oxidation method have attracted the most attention. The current carbon material oxidation methods mainly include nitric acid oxidation method, high-temperature calcination method and plasma treatment method. The literature "Zhang H, Li Y, Zhao Y, et al. Carbon black oxidized by air calcination for enhanced H2O2generation and effective organics degradation[J]. ACS Applied Materials &Interfaces, 2019, 11(31): 27846-27853." reported a method of air calcining oxidized carbon black for electrocatalytic oxygen reduction to produce H2O2. The reaction conditions were heating at 600℃ in a muffle furnace under air atmosphere for 1h. The 2e - ORR selectivity is less than 80%. The 2e - ORR performance needs to be improved. Moreover, these methods usually require a large amount of energy (electricity, heat) during operation, and may also be accompanied by a large amount of reaction waste (nitric acid, etc.), causing secondary pollution. Therefore, a green synthesis method that can oxidize carbon materials under relatively mild conditions is urgently needed to prepare efficient 2e - ORR electrocatalysts do not generate waste and are scalable, easy to control, safe and reliable. Summary of the invention

[0005] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide an oxygen-doped carbon material catalyst and a preparation method and application thereof.

[0006] The technical solution of the present invention to solve the technical problem of the method is to provide a method for preparing an oxygen-doped carbon material catalyst, characterized in that the method comprises the following steps: Step 1, grinding the carbon material to obtain a ground carbon material; Step 2: placing the ground carbon material in a reaction container; then continuously introducing ozone into the reaction container and adjusting the reaction temperature and relative humidity to oxidize the carbon material, and obtaining an oxygen-doped carbon material catalyst after the oxidation is completed.

[0007] The technical solution of the present invention to solve the technical problem of the catalyst is to provide an oxygen-doped carbon material catalyst prepared by the preparation method, characterized in that the mass fraction of oxygen in the oxygen-doped carbon material catalyst is 2~20%.

[0008] The technical solution of the present invention to solve the application technical problem is to provide an application of the oxygen-doped carbon material catalyst in the preparation of hydrogen peroxide by electrocatalytic oxygen reduction reaction.

[0009] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts the ozone oxidation method, and by adjusting the ozone concentration, reaction temperature, reaction time, gas humidity and other conditions, the proportion of oxygen-containing functional groups in the carbon material is precisely controlled, the degree of oxidation is controlled, and the catalytic performance is adjusted and optimized.

[0010] (2) The present invention uses low-concentration ozone oxidation to replace traditional high temperature and / or chemical reagents to oxidatively modify carbon materials. The ozone oxidation reaction conditions are mild, and the changes in the functional groups on the catalyst surface can be monitored in real time during the reaction. At the same time, the high specific surface area and high conductivity of the carbon material itself are maintained, which is conducive to the high efficiency of electrocatalytic activity. The reaction cost is low and does not involve harsh reaction conditions such as high temperature, high pressure, strong acid, and strong base. The synthesis process is simple and efficient, the process is controllable, no post-processing process is required, and the resulting product has almost no quality loss.

[0011] (3) The present invention only involves the oxidation of carbon materials, has low cost, does not contain metal elements, does not cause ion dissolution during use, and has better safety.

[0012] (4) Compared with traditional methods for preparing oxygen-doped carbon materials, such as nitric acid reflux oxidation and high-temperature calcination, this method has simple operation steps and low energy consumption. It can oxidize specific parts without causing structural changes and defects. It only involves changes in the oxygen content in the carbon material and can achieve precise control of the oxidation effect.

[0013] (5) The ozone oxidation process of carbon materials does not produce additional pollutants, and the exhaust gas can be purified greenly using industrial catalysts or heating, which meets the development requirements of green chemistry.

[0014] (6) This method has simple operation steps, efficient synthesis, controllable process, precise and adjustable conditions, and can be mass-produced, making it suitable for industrial production and application.

[0015] (7) The performance of the catalyst of the present invention was tested by an electrochemical workstation and a rotating ring disk electrode, and it has a good 2e - The ORR catalytic performance has a selectivity of 91% for hydrogen peroxide and exhibits good catalytic stability. It is suitable for large-scale production promotion and application and has broad development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a transmission electron microscope photograph of the ground carbon black of Example 1 of the present invention; Figure 2 This is a transmission electron microscope photograph of the oxygen-doped carbon black catalyst of Example 1 of the present invention; Figure 3 This is a Raman spectrum of the ground carbon black of Example 1 of the present invention; Figure 4 This is a Raman spectrum of the oxygen-doped carbon black catalyst of Example 1 of the present invention; Figure 5 is the X-ray diffraction pattern of the ground carbon black of Example 1 of the present invention; Figure 6 is an X-ray diffraction pattern of the oxygen-doped carbon black catalyst of Example 1 of the present invention; Figure 7 The graph is a relationship between the selectivity of hydrogen peroxide and the voltage of the ground carbon black and oxygen-doped carbon black catalyst in the oxygen reduction reaction according to Example 1 of the present invention; Figure 8 This is a curve diagram showing the relationship between the selectivity of hydrogen peroxide and the voltage of the oxygen-doped carbon black catalyst in the oxygen reduction reaction of Comparative Example 1 of the present invention; Fig. 9 This is a Raman spectrum of the oxygen-doped carbon black catalyst of Example 2 of the present invention; Fig.10 This is a Raman spectrum of the oxygen-doped carbon black catalyst of Example 3 of the present invention; Fig.11 This is a Raman spectrum of the oxygen-doped carbon black catalyst of Example 4 of the present invention; Fig.12 This is a Raman spectrum of the oxygen-doped carbon black catalyst of Example 5 of the present invention; Fig.13 This is a Raman spectrum of the oxygen-doped carbon black catalyst of Example 6 of the present invention; Fig.14 This is a Raman spectrum of the oxygen-doped carbon black catalyst of Example 7 of the present invention. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the present invention.

[0018] The present invention provides a method for preparing an oxygen-doped carbon material catalyst (hereinafter referred to as the method), characterized in that the method comprises the following steps: Step 1, grinding the carbon material to obtain a ground carbon material; Preferably, in step 1, the carbon material is at least one of carbon black, activated carbon, acetylene black, carbon nanotubes or Ketjen black.

[0019] Preferably, in step 1, the particle size of the ground carbon material is 30-60 nm, and the grinding time is 20-40 min.

[0020] Step 2: placing the ground carbon material in a reaction container; then continuously introducing ozone into the reaction container and adjusting the reaction temperature and relative humidity to oxidize the carbon material, and obtaining an oxygen-doped carbon material catalyst after the oxidation is completed.

[0021] Preferably, in step 2, the reaction container is a double-mouth container, preferably a quartz tube.

[0022] Preferably, in step 2, the ground carbon material occupies 1 to 50% (preferably 1 to 20%) of the volume of the reaction container.

[0023] Preferably, in step 2, the ratio of the concentration of ozone to the mass of the ground carbon material is 5-100 ppm:1 mg, preferably 20-40 ppm:1 mg, and more preferably 30 ppm:1 mg.

[0024] Preferably, in step 2, the flow rate of ozone is 50-1000 mL / min, preferably 100-600 mL / min, more preferably 100-300 mL / min, more preferably 100 mL / min.

[0025] Preferably, in step 2, the oxidation temperature is 10-70°C (preferably 20-30°C), the time is 0.1-12h (preferably 2-5h, more preferably 3h), and the relative humidity is 0-80% (preferably 20-60%, more preferably 40-60%, more preferably 50%).

[0026] Preferably, step 2 is specifically as follows: the two ends of the reaction container are respectively an air inlet end and an air outlet end, quartz wool is arranged at both ends, and the air inlet end is divided into an ozone gas circuit and an inert gas circuit; the outlet of the ozone generator is connected to the ozone gas circuit; the inert gas is introduced into the water-containing washing bottle, and the outlet of the water-containing washing bottle is connected to the inert gas circuit; after the connection is completed, the reaction temperature is set, the ozone generator is started and the inert gas is started to be introduced into the water-containing washing bottle, the inert gas carries water vapor into the reaction container, the relative humidity is adjusted by controlling the flow rate ratio of ozone to the inert gas, and the ozone concentration is adjusted by controlling the length of the light shield in the ozone generator; after the setting is completed, the carbon material is oxidized in an environment with a constant ozone concentration, constant temperature and humidity; after the oxidation is completed, the ozone generator is turned off, the introduction of inert gas and ozone is stopped, and the product is taken out after cooling to room temperature to obtain an oxygen-doped carbon material catalyst; wherein the inert gas is nitrogen, argon or helium.

[0027] The present invention also provides an oxygen-doped carbon material catalyst prepared by the preparation method, characterized in that the mass fraction of oxygen in the oxygen-doped carbon material catalyst is 2-20%.

[0028] The present invention also provides an application of the oxygen-doped carbon material catalyst in the preparation of hydrogen peroxide by electrocatalytic oxygen reduction reaction (preferably applied to the preparation of hydrogen peroxide by two-electron oxygen reduction reaction), specifically: using an electrochemical workstation as an electrochemical test generating device, adopting a three-electrode measurement system, coating the oxygen-doped carbon material catalyst on the glassy carbon surface of a rotating ring disk electrode as a working electrode, using a platinum sheet and a mercury / mercury oxide electrode as a counter electrode and a reference electrode respectively, using a potassium hydroxide aqueous solution as an electrolyte, continuously introducing oxygen into the electrolyte, energizing the electrodes for an electrochemical oxygen reduction reaction, and producing hydrogen peroxide on the working electrode, wherein the concentration of the potassium hydroxide aqueous solution is 0.05-0.2 mol / L.

[0029] The testing method of the embodiment is: using a transmission electron microscope to analyze the material to obtain its transmission electron microscope photo, using a Raman spectrometer to analyze the material to obtain its Raman spectrum, and using an X-ray diffractometer to analyze the material to obtain its X-ray diffraction pattern.

[0030] Example 1 (1) Grind 20 mg of carbon black in a mortar for 30 min to obtain ground carbon black with a particle size of 30 to 60 nm; (2) The ground carbon black was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 600 ppm was continuously introduced into the quartz tube at a flow rate of 100 mL / min, and the reaction temperature was adjusted to 25°C and the relative humidity was adjusted to 50%. The carbon black was oxidized for 3 hours. After the oxidation was completed, an oxygen-doped carbon black catalyst was obtained.

[0031] Depend on Figure 1 It can be seen that the ground carbon black is relatively regular round particles with a size of about 50 nm and relatively rough particle edges.

[0032] Depend on Figure 2 It can be seen that the morphology and size of the oxygen-doped carbon black catalyst remain unchanged compared to the ground carbon black, and the particle edges are relatively smooth.

[0033] Depend on Figure 1 and Figure 2 By comparison, it can be seen that the surface morphology of the carbon material has changed significantly after being oxidized by ozone.

[0034] Depend on Figure 3 It can be seen that two characteristic peaks of carbon materials appear in the Raman spectrum of the ground carbon black, which are used to characterize the defect characteristics of carbon black.

[0035] Depend on Figure 4 It can be seen that after oxidation by ozone, the peak intensity ratio of the two peaks in the Raman spectrum of carbon black remains unchanged.

[0036] Depend on Figure 3 and Figure 4 By comparison, it can be seen that the degree of defects of carbon black did not change before and after ozone treatment.

[0037] Depend on Figure 5 It can be seen that the X-ray diffraction pattern of the ground carbon black shows the characteristic diffraction peaks of carbon materials.

[0038] Depend on Figure 6 It can be seen that the diffraction pattern of the oxygen-doped carbon black catalyst did not change significantly, indicating that ozone oxidation does not change the crystallinity of the carbon material.

[0039] contrast Figure 1-6 It can be seen that ozone treatment will cause morphological changes on the surface of carbon materials but will not create more defect sites.

[0040] Verify the electrocatalytic performance of the catalyst of Example 1: Prepare a dispersion liquid with the catalyst of Example 1: weigh 5 mg of the catalyst, add 975 μL of anhydrous ethanol and 25 μL of 5% Nafion solution, and ultrasonicate for 45 min until the catalyst is evenly dispersed to obtain the catalyst dispersion liquid of Example 1. Take 10 μL of the catalyst dispersion droplets and apply them on the glassy carbon surface of the rotating ring disk electrode, and dry at room temperature to form a working electrode.

[0041] An electrochemical workstation was used as the electrochemical test generating device, and a three-electrode measurement system was adopted. A rotating ring disk electrode coated with a catalyst was used as the working electrode, a platinum sheet and a mercury / mercury oxide electrode were used as the counter electrode and the reference electrode, respectively. A 0.1 mol / L potassium hydroxide aqueous solution was used as the electrolyte. Before the test, oxygen was continuously introduced into the electrolyte for 30 min at an oxygen flow rate of 100 mL / min. The electrodes were then energized for an electrochemical oxygen reduction reaction, and hydrogen peroxide was produced on the working electrode. The voltage range of the selective oxygen reduction test was 0.3~0.7 V (vs. RHE), the rotation speed was 1600 rpm, and the scanning speed was 5 mV / s. The data were all collected after the scanning current was stable.

[0042] 2e of cathode materials - The formula for calculating the ORR electrocatalytic selectivity is: H2O2%=(200I R / N) / (I D +I R / N), where IR and ID represent the ring current and disk current in the rotating ring disk electrode, respectively, and N represents the collection coefficient of the platinum ring of the rotating ring disk electrode during the test, which is measured to be 0.252.

[0043] Depend on Figure 7 It can be seen that the present invention has a significant improvement effect on the ORR activity of carbon materials, 2e - The ORR electrocatalytic selectivity is greatly improved, up to 91%, which verifies the application potential of the present invention.

[0044] Comparative Example 1 Referring to the reported literature "Xia C, Xia Y, Zhu P, et al. Direct electrosynthesis of pure aqueous H2O2 solutions up to 20% by weight using a solid electrolyte[J]. Science, 2019, 366(6462): 226-231.", the specific method is: grind 20 mg of carbon black and add it to 20 mL of concentrated nitric acid solution (68 wt%), heat the reaction at 85 °C for 12 h under stirring at 200 rpm, cool to room temperature, centrifuge at 8000 rpm for 3 min, then wash with deionized water until the pH is neutral, wash with anhydrous ethanol three times, and vacuum dry at 70 °C for 12 h to obtain the oxygen-doped carbon black catalyst.

[0045] The electrocatalytic performance of the catalyst of Comparative Example 1 was verified using the same method as Example 1.

[0046] contrast Figure 7 and Figure 8 It can be seen that compared with the nitric acid oxidation method reported in the existing literature, the carbon material obtained by ozone treatment in the present invention has a better 2e - ORR activity and selectivity demonstrate the excellent performance of ozone treatment.

[0047] Example 2 (1) Grind 20 mg of carbon black in a mortar for 30 min to obtain ground carbon black with a particle size of 30 to 60 nm; (2) The ground carbon black was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 200 ppm was continuously introduced into the quartz tube at a flow rate of 100 mL / min, and the reaction temperature was adjusted to 25°C and the relative humidity was adjusted to 50%. The carbon black was oxidized for 3 hours. After the oxidation was completed, an oxygen-doped carbon black catalyst was obtained.

[0048] Depend on Fig. 9 It can be seen that after oxidation by ozone, the peak intensity ratio of the two peaks in the Raman spectrum of carbon black remains unchanged.

[0049] The electrocatalytic performance of the catalyst of Example 2 was verified by the same method as Example 1. After testing, the 2e- The ORR selectivity can reach up to 82%.

[0050] Example 3 (1) Grind 20 mg of carbon black in a mortar for 30 min to obtain ground carbon black with a particle size of 30 to 60 nm; (2) The ground carbon black was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 400 ppm was continuously introduced into the quartz tube at a flow rate of 100 mL / min, and the reaction temperature was adjusted to 25°C and the relative humidity was adjusted to 50%. The carbon black was oxidized for 3 hours. After the oxidation was completed, an oxygen-doped carbon black catalyst was obtained.

[0051] Depend on Fig.10 It can be seen that after oxidation by ozone, the peak intensity ratio of the two peaks in the Raman spectrum of carbon black remains unchanged.

[0052] The electrocatalytic performance of the catalyst of Example 3 was verified by the same method as Example 1: After testing, the 2e - The ORR selectivity can reach up to 87%.

[0053] Example 4 (1) Grind 20 mg of carbon black in a mortar for 30 min to obtain ground carbon black with a particle size of 30 to 60 nm; (2) The ground carbon black was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 800 ppm was continuously introduced into the quartz tube at a flow rate of 100 mL / min, and the reaction temperature was adjusted to 25°C and the humidity was 50%. The carbon black was oxidized for 3 hours. After the oxidation was completed, an oxygen-doped carbon black catalyst was obtained.

[0054] Depend on Fig.11 It can be seen that after oxidation by ozone, the peak intensity ratio of the two peaks in the Raman spectrum of carbon black remains unchanged.

[0055] The electrocatalytic performance of the catalyst of Example 4 was verified by the same method as in Example 1. After testing, the 2e - The ORR selectivity can reach up to 86%.

[0056] Example 5 (1) Grind 20 mg of carbon black in a mortar for 30 min to obtain ground carbon black with a particle size of 30 to 60 nm; (2) The ground carbon black was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 1000 ppm was continuously introduced into the quartz tube at a flow rate of 100 mL / min, and the reaction temperature was adjusted to 25°C and the humidity was 50%. The carbon black was oxidized for 3 hours. After the oxidation was completed, an oxygen-doped carbon black catalyst was obtained.

[0057] Depend on Fig.12 It can be seen that after oxidation by ozone, the peak intensity ratio of the two peaks in the Raman spectrum of carbon black remains unchanged.

[0058] The electrocatalytic performance of the catalyst of Example 5 was verified by the same method as Example 1: After testing, the 2e - The ORR selectivity can reach up to 83%.

[0059] Example 6 (1) Grind 20 mg of carbon black in a mortar for 30 min to obtain ground carbon black with a particle size of 30 to 60 nm; (2) The ground carbon black was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was placed at both ends of the quartz tube; then, ozone with a concentration of 600 ppm was continuously introduced into the quartz tube at a flow rate of 100 mL / min, and the reaction temperature was adjusted to 25°C and the humidity to 50%. The carbon black was oxidized for 1 hour, and after the oxidation was completed, an oxygen-doped carbon black catalyst was obtained.

[0060] Depend on Fig.13 It can be seen that after oxidation by ozone, the peak intensity ratio of the two peaks in the Raman spectrum of carbon black remains unchanged.

[0061] The electrocatalytic performance of the catalyst of Example 6 was verified by the same method as in Example 1. After testing, the 2e - The ORR selectivity can reach up to 83%.

[0062] Example 7 (1) Grind 20 mg of carbon black in a mortar for 30 min to obtain ground carbon black with a particle size of 30 to 60 nm; (2) The ground carbon black was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 600 ppm was continuously introduced into the quartz tube at a flow rate of 100 mL / min, and the reaction temperature was adjusted to 25°C and the humidity was 50%. The carbon black was oxidized for 5 hours. After the oxidation was completed, an oxygen-doped carbon black catalyst was obtained.

[0063] Depend on Fig.14 It can be seen that after oxidation by ozone, the peak intensity ratio of the two peaks in the Raman spectrum of carbon black remains unchanged.

[0064] The electrocatalytic performance of the catalyst of Example 7 was verified by the same method as Example 1: After testing, the 2e - The ORR selectivity can reach up to 85%.

[0065] Depend on Figure 9-14 It can be seen that changes in the ozone oxidation treatment conditions do not affect the overall structure of the carbon material.

[0066] The oxygen-doped carbon black catalysts in Examples 1-7 were analyzed using an X-ray photoelectron spectrometer to obtain the carbon-oxygen content ratio in the material, as shown in Table 1.

[0067]

[0068] By comparison, it can be seen that ozone treatment has a significant effect on the oxygen doping modification of carbon materials, and with the increase of ozone concentration and treatment time, the oxygen content in the carbon material gradually increases, which proves the feasibility of ozone treatment for carbon material modification.

[0069] Example 8 (1) Grind 20 mg of activated carbon in a mortar for 20 min to obtain ground activated carbon with a particle size of 30-60 nm; (2) The ground activated carbon was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 600 ppm was continuously introduced into the quartz tube at a flow rate of 50 mL / min, and the reaction temperature was adjusted to 65 ° C and the humidity was 80%. The carbon black was oxidized for 0.5 h. After the oxidation was completed, an oxygen-doped activated carbon catalyst was obtained.

[0070] The electrocatalytic performance of the catalyst of Example 8 was verified by the same method as in Example 1. - The ORR selectivity can reach up to 81%.

[0071] Example 9 (1) Grind 20 mg of acetylene black in a mortar for 40 min to obtain acetylene black with a particle size of 30 to 60 nm; (2) The ground acetylene black is placed in a quartz tube with an inner diameter of 6 mm, and quartz wool is set at both ends of the quartz tube; then, ozone with a concentration of 600 ppm is continuously introduced into the quartz tube at a flow rate of 1000 mL / min, and the reaction temperature is adjusted to 10°C and the humidity is 5%. The carbon black is oxidized for 12 hours. After the oxidation is completed, an oxygen-doped acetylene black catalyst is obtained.

[0072] The electrocatalytic performance of the catalyst of Example 9 was verified by the same method as in Example 1. - The ORR selectivity can reach up to 85%.

[0073] Example 10 (1) Grind 20 mg of carbon nanotubes in a mortar for 20 min to obtain ground carbon nanotubes with a particle size of 30 to 60 nm; (2) The ground carbon nanotubes were placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was placed at both ends of the quartz tube; then, ozone with a concentration of 600 ppm was continuously introduced into the quartz tube at a flow rate of 200 mL / min, and the reaction temperature was adjusted to 45°C and the humidity to 50%. The carbon black was oxidized for 5 hours. After the oxidation was completed, an oxygen-doped carbon nanotube catalyst was obtained.

[0074] The electrocatalytic performance of the catalyst of Example 10 was verified by the same method as in Example 1. - The ORR selectivity can reach up to 89%.

[0075] Embodiment 11 (1) Grind 20 mg of carbon nanotubes and Ketjen black in a mortar for 20 min to obtain a ground carbon material with a particle size of 30 to 60 nm; (2) The ground carbon material was placed in a quartz tube with an inner diameter of 6 mm, and quartz wool was set at both ends of the quartz tube; then, ozone with a concentration of 600 ppm was continuously introduced into the quartz tube at a flow rate of 300 mL / min, and the reaction temperature was adjusted to 25°C and the humidity was 50%. The carbon black was oxidized for 3 hours. After the oxidation was completed, an oxygen-doped carbon material catalyst was obtained.

[0076] The electrocatalytic performance of the catalyst of Example 11 was verified by the same method as in Example 1. - The ORR selectivity can reach up to 88%.

[0077] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for preparing an oxygen-doped carbon material catalyst, characterized in that: The method comprises the following steps: Step 1, grinding the carbon material to obtain a ground carbon material; Step 2: placing the ground carbon material in a reaction container; then continuously introducing ozone into the reaction container and adjusting the reaction temperature and relative humidity to oxidize the carbon material, and obtaining an oxygen-doped carbon material catalyst after the oxidation is completed.

2. The method for preparing an oxygen-doped carbon material catalyst according to claim 1, characterized in that: In step 1, the carbon material is at least one of carbon black, activated carbon, acetylene black, carbon nanotubes or Ketjen black.

3. The method for preparing an oxygen-doped carbon material catalyst according to claim 1, characterized in that: In step 1, the particle size of the ground carbon material is 30-60 nm, and the grinding time is 20-40 min.

4. The method for preparing an oxygen-doped carbon material catalyst according to claim 1, characterized in that: In step 2, the ground carbon material occupies 1 to 50% of the volume of the reaction container.

5. The method for preparing an oxygen-doped carbon material catalyst according to claim 1, characterized in that: In step 2, the ratio of the concentration of ozone to the mass of the ground carbon material is 5-100 ppm:1 mg.

6. The method for preparing an oxygen-doped carbon material catalyst according to claim 1, characterized in that: In step 2, the flow rate of ozone is 50-1000 mL / min.

7. The method for preparing an oxygen-doped carbon material catalyst according to claim 1, characterized in that: In step 2, the oxidation temperature is 10-70° C., the oxidation time is 0.1-12 h, and the relative humidity is 0-80%.

8. The method for preparing an oxygen-doped carbon material catalyst according to claim 1, characterized in that: Step 2 is specifically as follows: the two ends of the reaction container are respectively an air inlet end and an air outlet end, and the air inlet end is divided into an ozone gas circuit and an inert gas circuit; the outlet of the ozone generator is connected to the ozone gas circuit; the inert gas is introduced into the water-containing washing bottle, and the outlet of the water-containing washing bottle is connected to the inert gas circuit; after the connection is completed, the reaction temperature is set, the ozone generator is started and the inert gas is started to be introduced into the water-containing washing bottle, the inert gas carries water vapor into the reaction container, the relative humidity is adjusted by controlling the flow rate ratio of ozone to inert gas, and the ozone concentration is adjusted by controlling the ozone generator; after the setting is completed, the carbon material is oxidized in an environment with a constant ozone concentration, constant temperature and humidity; after the oxidation is completed, the ozone generator is turned off, the introduction of inert gas and ozone is stopped, and the product is taken out after cooling to room temperature to obtain an oxygen-doped carbon material catalyst; The inert gas is nitrogen, argon or helium.

9. An oxygen-doped carbon material catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: In oxygen-doped carbon material catalysts, the mass fraction of oxygen is 2~20%.

10. Use of the oxygen-doped carbon material catalyst according to claim 9 in preparing hydrogen peroxide by electrocatalytic oxygen reduction reaction.